Applying Building Information Modelling Plus-the Practice of Shanghai Shipping Service Complex - Wang, Xuefeng; Wang, Yibo; Ge, Jiawei; Wu, Pengcheng; Huang, Tianrong (Review of Industrial Engineering Letters, 2018)
Taking advantage of Building Information Model (BIM) to integrate multi-dimensional information, such as time and space information can provide robust guidance for design, construction and operation management, which can produce strong technical support for improving project management. Based on the BIM+ theory and the ship lock construction in Shanghai Shipping Service Complex (SSSC), this paper formulates the stages and contents of the application of BIM technology. Through the implementation of BIM in the planning, design, construction and maintenance of ship lock engineering, the management of the whole life cycle of the project are realised. The application of BIM+ theory in SSSC lock engineering is explored effectively by 3D printing technology combined with Internet technology.